Influence of Heat and Mechanical Treatments on the Mechanical and Structural Characteristics of Molded Manganese Steels - Ben Lenda, Omar; El Ganich, Hajar; Benmaziane, Sara; Saad, Elmadani (Directorate for Research and Community Services, Institut Teknologi Bandung, 2026)
This paper presents a study to improve the performance of Fe-Mn-C cast steels containing 1.7% and 2.7% Cr by weight, using two treatment methods (thermal and mechanical) applied separately to two different steel grades. This approach enables an extended service life for components such as crusher liners, mill hammers, and level crossings, without requiring complete recasting. The experimental techniques used for characterization included spark optical emission spectroscopy, optical microscopy, scanning electron microscopy, as well as micro- and macro-hardness testing. Steel 1, with a composition of 15.51% Mn, 2.68% Cr, and 1.29% C, was heat-treated at 1070 °C and quenched in water, using different holding times and thicknesses. It was found that increasing the holding time from 30 to 50 minutes and reducing the thickness from 150 to 100 millimeters led to a complete and homogeneous dissolution of carbides. As a result, Steel 1 exhibited increased ductility. Steel 2 contains 13.45% Mn, 1.72% Cr, and 1.21% C. It underwent manual mechanical treatment, which resulted in surface hardening due to the transformation of austenite into martensite.